Internalisasi Nilai Sense Of Efficiency dalam Pembentukan Budaya Industri di SMK Mikael Surakarta - Mikael Dimas Mahardika; Valiant Lukad Perdana Sutrisno (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
Vocational education plays an important role in preparing human resources who are not only technically competent but also possess work characteristics aligned with industrial culture. One important industrial value that needs to be internalized is Sense of Efficiency, which emphasizes effective and optimal utilization of time, energy, tools, and materials without compromising work quality. This study aims to analyze the internalization process of the Sense of Efficiency value in shaping industrial culture at SMK Mikael Surakarta. This study employed a qualitative case study approach involving school management, workshop coordinators, practical teachers, and twelfth-grade students selected through purposive and snowball sampling techniques. Data were collected through semi-structured interviews and analyzed using the interactive model of Miles and Huberman, while data validity was ensured through source triangulation. The findings indicate that the internalization of Sense of Efficiency is implemented gradually through time discipline, work preparation, optimization of tools and materials, and time-based work evaluation. The process is strengthened through a block learning system, industrial-based practical environments, and teachers’ active roles in guiding students toward effective work habits. This study concludes that the cultivation of efficiency values in vocational education contributes to strengthening students’ work readiness in responding to industrial productivity demands.